Climate Politics, Justice, and Efficiency. Key Issues in Creating Social Acceptance for Energy Transformations - Johannes Müller-Salo; Rupert Pritzl (Wirtschaftsdienst)
Abstract Climate policies should meet the requirements of justice as well as those of efficiency. In order to achieve both goals, the choice of instruments is of central importance. However, German climate policy focuses on announcing newer, more ambitious targets and meanwhile neglects serious discussions about costs and adequate instruments. Such a structure and culture of political discourse is detrimental to the social acceptance of sustainable energy policy and energy transformation. Moreover, the crucial importance of international climate policy is hardly noticed.